PENGARUH ENTREPRENEURIAL LEADERSHIP TERHADAP KINERJA UMKM KOTA SURABAYA MELALUI INOVASI - Yulvi Yusnia Anggriani; Anang Kistyanto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2021)
The economic movement in East Java which was dominated by MSMEs until December 2016 was able to increase the economy in Surabaya with many of these business people. This study aims to examine and analyze the effect of entrepreneurial leadership on organizational performance mediated by innovation in MSMEs guided by Cooperative Agency and Micro Enterprise City of Surabaya with Food and Beverage Business Sector. The type of this research is quantitative and explanatory research. The population of this research is the MSMEs guided by Dinas Koperasi dan Usaha Mikro Kota Surabaya with the Food and Beverage Business Sector. The questionnaire was distributed to 35 respondents and the statistical analysis used was Partial Least Squares (PLS) with smartPLS 3.0 software. The results of this study explain that entrepreneurial leadership has a significant positive effect on organizational performance. Entrepreneurial leadership has a significant positive effect on product innovation. Product innovation does not affect organizational performance. Entrepreneurial leadership does not affect organizational performance through product innovation. There is still inconsistency between this research result and previous research, the next research should analyze others variables that might affect entrepreneurial leadership in different sector.